The picture of Dorian Gray [compact disc, unabridged] - Wilde, Oscar, 1854-1900 (Tantor Media, 2008)
Young, handsome Dorian Gray, after having his portrait painted, sits admiring the artist's rendering. It is then that he makes a wish for the portrait to change as he ages, but for his actual visage to stay the same. He gets his wish, and despite his hedonistic, sinful lifestyle, Dorian remains young and innocent looking. As those around him witness his excessive habits, they wonder if Dorian Gray will ever get his just dues.